Developing predictive rules for coordination geometry from visible circular dichroism of copper(II) and nickel(II) ions in histidine and amide main‐chain complexes. (11th August 2014) - Stanyon, Helen F.; Cong, Xiaojing; Chen, Yan; Shahidullah, Nabeela; Rossetti, Giulia; Dreyer, Jens; Papamokos, George; Carloni, Paolo; Viles, John H.
<x xml:space="preserve">Abstract</x> Circular dichroism (CD) spectroscopy in the visible region (vis‐CD) is a powerful technique to study metal–protein interactions. It can resolve individual d–d electronic transitions as separate bands and is particularly sensitive to the chiral environment of the transition metals. Modern quantum chemical methods enable CD spectra calculations from which, along with direct comparison with the experimental CD data, the conformations and the stereochemistry of the metal–protein complexes can be assigned. However, a clear understanding of the observed spectra and the molecular configuration is largely lacking. In this study, we compare the experimental and computed vis‐CD spectra of Cu2+‐loaded model peptides in square‐planar complexes. We find that the spectra can readily discriminate the coordination pattern of Cu2+ bound exclusively to main‐chain amides from that involving both main‐chain amides and a side‐chain (i.e. histidine side‐chain). Based on the results, we develop a set of empirical rules that relates the appearance of particular vis‐CD spectral features to the conformation of the complex. These rules can be used to gain insight into coordination geometries of other Cu2+–or Ni2+–protein complexes.